MicroRNA-3653-3p inhibited papillary thyroid carcinoma progression by regulating CRIPTO-1: miR-3653-3p in papillary thyroid carcinoma - Bai, Xiaojun; Xu, Yanjun; Liu, Yilun (Cellular and Molecular Biology, 2023)
Papillary thyroid carcinoma (PTC) is the most common endocrine malignant tumor and the metastasis of PTC often leads to unfavorable prognosis. Thus, the purpose of the current research was to mainly explore the role of miR-3653-3p in PTC progression. The expression level of miR-3653-3p in PTC was determined by quantitative Real Time-Polymerase Chain Reaction (qRT-PCR), and Cell Counting Kit-8 (CCK-8) assay and colony formation assay were recruited to assess the ability of miR-3653-3p on cell proliferation. Next, transwell assay and Matrigel assay were involved to examine the ability of miR-3653-3p on cell migration and invasion. At last, Dual-Luciferase reporter assay and Western blotting were recruited to validate the down-stream target of miR-3653-3p. Results showed that miR-3653-3p was down-expressed in PTC, and upregulated miR-3653-3p inhibited cell proliferation, cell migration, and cell invasion in vitro. In addition, CRIPTO-1 was a downstream target of miR-3653-3p, and miR-3653-3p inhibited PTC progression via regulating CRIPTO-1. In sum, this research verifies that miR-3653-3p suppresses cell proliferation, migration, and invasion in PTC via regulating CRIPTO-1. These findings provide new insight into the underlying mechanism of PTC progression and may be useful in finding biomarkers and therapeutic targets of PTC.